Development and Effectiveness of Augmented Reality Learning Media to Enhance Vocational Education Quality in Roof Construction - Hufa Weno Artha; Nurhasan Syah; Giatman; Ika Parma Dewi (Postgraduate, University of Mataram, 2026)
Insufficient conceptual understanding of roof construction elements often leads to suboptimal learning outcomes in vocational education. The technical nature of structural components requires high spatial visualization, which conventional materials fail to provide. This study aimed to develop valid, practical, and effective augmented reality learning media to bridge this gap. Utilizing the ADDIE model (analysis, design, development, implementation, and evaluation), the research involved three-dimensional structural modeling and smartphone integration. Testing was conducted at SMK Negeri 5 Padang involving an experimental class (n = 32) and a control class (n = 12) within the Fundamentals of Construction and Housing Engineering subject. Data were gathered through validation sheets, practicality questionnaires, and pre-test post-test instruments. Results indicated high validity scores of 4.71 from media matter experts and 4.63 from subject experts, with practicality ratings of 95.76 percent from teachers and 93.00 percent from students. Statistical analysis via independent t-test revealed significant differences in post-test scores (t = 2.24, p = 0.03). Furthermore, the experimental group achieved a higher competency growth (N-gain 0.66) than the control group (0.51, p = 0.01). In conclusion, augmented reality is highly feasible for enhancing vocational learning outcomes by transforming abstract references into interactive visualizations.